Toxoplasma Seroprevalence in Healthy Voluntary Blood Donors from Blood Bank of Baghdad - Aysar Essam Mahmood; Zainb Mohammad Etawi; Mayssa Abdul-Latif Ahmed (College of Pharmacy / Mustansiriyah University, 2014)
In this study (300) blood samples were collected from healthy volunteer at national transfusion center, ministry of health, republic of Iraq, was examined for anti-Toxoplasma gondii antibodies by enzyme linked immunosorbent assay. The seroprevalence of anti-Toxoplasma gondii total IgG, IgM antibodies were 85 (56.6%), 40 (26.6%) respectively. While positive rate for IgG, IgM in female and male were 65 (43.3%), 35 (23.3%) and 20(13.3%), 5 (3.3%) respectively. The high positive rate of IgG and IgM appear in femle whoage rated between (21-30) and (31-40) years old, were 27 (25.7%), 7 (15.5%) respectively. Also rate of toxoplasmosis in married women greater than married men 27 (28.4%), 2 (1.9%).The same things for women cats breed, the rate of IgG and IgM was 24(44.4), higher thanmen who breed cats.